The role of influencer content value and credibility in purchase intention - Ahmad Shaheen; Abdullah Khataan; Abdelrehim Awad; Anwar Yahia Shams Eldin; Awadia Elnour (Innovative Marketing)
Influencer marketing is a prominent strategy for engaging young consumers via social media. This study aimed to explore the effects of different dimensions of influencer value of content and influencer credibility on purchase intention among young Egyptian adult consumers. Employing a descriptive-explanatory design, survey data were collected from 633 social media users. Analysis via Structural Equation Modeling (SEM) revealed that all examined dimensions of influencer content value significantly and positively influence purchase intention, with entertainment value (r = 0.878 in correlation analysis, SEM estimate = 0.150) and functional value (r = 0.819 in correlation, SEM estimate = 0.118) demonstrating particularly strong contributions. Regarding influencer credibility, perceived trustworthiness (r = 0.918 in correlation, SEM estimate = 0.218) and perceived similarity (r = 0.923 in correlation, SEM estimate = 0.280) exhibited the most substantial positive impacts on purchase intention; perceived expertise and attractiveness also yielded significant, albeit comparatively moderate, effects. These findings underscore the critical, differentiated roles of specific content value and credibility facets in shaping consumer purchase decisions within the Egyptian youth market, offering actionable insights for optimizing influencer marketing strategies. AcknowledgmentThe authors are thankful to the Deanship of Graduate Studies and Scientific Research at University of Bisha for supporting this work through the Fast-Track Research Support Program.